Perfect Secrecy in IoT A Hybrid Combinatorial-Boolean Approach - Zolfaghari, Behrouz; Bibak, Khodakhast (Cham : Springer International Publishing : Imprint: Springer, 2022)
Perfectly-secure cryptography is a branch of information-theoretic cryptography. A perfectly-secure cryptosystem guarantees that the malicious third party cannot guess anything regarding the plain text or the key, even in the case of full access to the cipher text. Despite this advantage, there are only a few real-world implementations of perfect secrecy due to some well-known limitations. Any simple, straightforward modeling can pave the way for further advancements in the implementation, especially in environments with time and resource constraints such as IoT. This book takes one step towards this goal via presenting a hybrid combinatorial-Boolean model for perfectly-secure cryptography in IoT. In this book, we first present an introduction to information-theoretic cryptography as well as perfect secrecy and its real-world implementations. Then we take a systematic approach to highlight information-theoretic cryptography as a convergence point for existing trends in research on cryptography in IoT. Then we investigate combinatorial and Boolean cryptography and show how they are seen almost everywhere in the ecosystem and the life cycle of information-theoretic IoT cryptography. We finally model perfect secrecy in IoT using Boolean functions, and map the Boolean functions to simple, well-studied combinatorial designs like Latin squares. This book is organized in two parts. The first part studies information-theoretic cryptography and the promise it holds for cryptography in IoT. The second part separately discusses combinatorial and Boolean cryptography, and then presents the hybrid combinatorial-Boolean model for perfect secrecy in IoT. It presents the first scheme for secret-algorithm perfectly-secure cryptography; It provides novel research on modeling perfect secrecy using resilient Boolean functions; It maps resilient Boolean functions to well-studied combinatorial constructs called Latin squares.
Introduction -- A Review on Perfect Secrecy -- Perfect Secrecy and Boolean Functions with Applications in Resource-Constrained IoT Environments -- Cryptography in IoT -- Resilient functions -- Modeling a General Cryptographic Algorithm -- Latin Squares and Cryptography -- Perfectly-Secure Encryption Modeled Using Latin Squares -- Conclusion.
Keywords: Telecommunication; Cooperating objects (Computer systems).; Data protection; Internet of things; Communications Engineering, Networks; Cyber-Physical Systems; Data and Information Security; Internet of Things